PENGARUH NON PERFORMING LOAN DAN LOAN TO DEPOSIT RATIO TERHADAP RETURN ON ASSETS PADA BANK BUMN PERIODE 2009-2019 - Setiyani, Suci Cicih Catur; Manda, Gusganda Suria (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.10.NO.03.TAHUN. 2021DO - 10.24843/EEB.2021.v10.i03.p04, 2021)
This Study aims to determine the effect of NPL and LDR on ROA in Bank BUMN listed on Indonesia Stock Exchange for the period of 2009-2019. The data used in this research is secondary data in the form of quatitative used saturated samples, so the number of observations was 4 banks and the sample obtained were 44 samples. The method in this research uses inferential analysis. The Analyze technique uses multiple linier regression analysis to determine the effect of NPL and LDR on ROA. The partial tet result show hat NPL has a sig value. 0,000 < 0,05 and t-count -4,602 > t table 2,01954 meaning that NPL has a negative and significant effect on ROA. LDR has a sig value 0,002 < 0,05 and t-count -3,299 > t-table 2,01954 meaning that LDR has a negative and significant effect on ROA. Simultaneously, menaning that NPL and LDR have a significant effect on ROA with sig. value = 0,000.